FUZZY-BASED ENGLISH WRITING WITH KEY-BASED ASSESSMENT - Janice Hill (Фізико-математична освіта)
Traditional assessment methods in education often rely on rigid grading structures that may fail to capture the nuances of language skills, especially in subjective areas like writing. This article explores how fuzzy logic, a mathematical system that handles imprecision, can enhance English writing assessment by providing a more flexible, holistic view of students' abilities.